Banking in East Africa - Engberg, Holger L. (New York, 1964)
Material for this work was collected during a visit to England and East Africa from June to September, 1963. A list is appended of the principal persons consulted in London and Kenya, Uganda, Tanganyika, and Zanzibar
osc 23/5/2018
Loans
Keywords: Banking; East Africa